2015
DOI: 10.1021/acs.chemmater.5b01542
|View full text |Cite
|
Sign up to set email alerts
|

Narrowly Distributed Crystal Orientation in Biomineral Vaterite

Abstract: Biominerals formed by animals provide skeletal support, and many other functions. They were previously shown to grow by aggregation of amorphous nanoparticles, but never to grow ion-by-ion from solution, which is a common growth mechanism for abiotic crystals. We analyze vaterite (CaCO3) multi-crystalline spicules from the solitary tunicate Herdmania momus, with Polarization-dependent Imaging Contrast (PIC)-mapping, scanning and aberration-corrected transmission electron microscopies. The first fully-quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 98 publications
(159 reference statements)
1
28
0
Order By: Relevance
“…In this case, however, one encounters polycrystalline material and rotation of nanocrystal orientation. The case of the recently reported biomineral vaterite is especially interesting and relevant11, because it exhibits orientation changes between adjacent crystallites within a narrow range of 0 to 30° without any organic interfacial layer that often contributes to the alignment of neighboring crystallites1213. This is a completely unexpected result from the classical theory of crystallization by nucleation and growth, and spherulitic growth mode has been suggested to explain these observations.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…In this case, however, one encounters polycrystalline material and rotation of nanocrystal orientation. The case of the recently reported biomineral vaterite is especially interesting and relevant11, because it exhibits orientation changes between adjacent crystallites within a narrow range of 0 to 30° without any organic interfacial layer that often contributes to the alignment of neighboring crystallites1213. This is a completely unexpected result from the classical theory of crystallization by nucleation and growth, and spherulitic growth mode has been suggested to explain these observations.…”
mentioning
confidence: 80%
“…However, its mechanism, in particular the source of non-crystallographic branching in spherulites remains unclear7. So the knowledge of how lattice rotation is introduced is important for understanding the formation of spherulites145671415161718192021222324 as well as biominerals910111213. The ability to control this rotation will help fabricate ‘bio-inspired’ materials that mimic the structure of biominerals and hence their superior properties25.…”
mentioning
confidence: 99%
“…The angular distance Δc is a direct measurement of misorientation between the c-axes of two adjacent crystals. 40 The histogram in Figure 7a clearly shows that almost all the pairs of adjacent crystals measured have an angular distance between 0°−30°, and the ) an SA spherulite. Two adjacent domains with homogeneous color in PIC-maps were selected and their angular distance Δc, that is, the difference in orientation of their c-axes were calculated as described in Figure S8 caption.…”
mentioning
confidence: 93%
“…38,39 Spherulitic growth was suspected to take place in vaterite spicules based on their crystal orientations. 40 Benzerara et al showed in a Porites coral skeleton a radial distribution of aragonite crystal orientations strongly suggestive of spherulitic structure, but did not explicitly conclude that it was spherulitic. 41 For all other biominerals, high resolution, quantitative crystal orientation analysis has not been done.…”
mentioning
confidence: 98%
“…As such, this concept could be associated, if not actually considered as interchangeable, with the notion of meso-crystals defined for the growth by oriented attachment of nanoparticles building up single crystals. 29 It also appears that a surface fractal aggregate model could explain various aspects of the concept of mosaicity that characterises the formation of inorganic [30][31][32] and macromolecular [33][34][35][36] single crystals.…”
Section: Introductionmentioning
confidence: 99%